Relationships between functional outcomes and symptomatic improvement in atomoxetine-treated adult patients with attention-deficit/hyperactivity disorder: post hoc analysis of an integrated database - Bruyckere, Katrien De; Dittmann, Ralf (CNS drugs, 2016)
Background: Atomoxetine treatment is associated with improvements in functional outcomes in patients with attention-deficit/hyperactivity disorder (ADHD), although relationships between improvements in these outcomes and reductions in ADHD symptoms have not been comprehensively investigated in adults. Objectives: The aim of this study was to assess relationships between functional outcomes and ADHD symptoms (primary objective), and to assess time courses of changes in functional outcomes from baseline to weeks 10 and 24 (secondary objective). Methods: We analyzed data pooled from seven Eli Lilly-sponsored placebo-controlled trials of atomoxetine in adults with ADHD that had Conners’ Adult ADHD Rating Scales-Investigator Rated: Screening Version (CAARS-Inv:SV) total scores and functional outcome data at baseline and at week 10. Two trials also had these data at week 24. Patients were included in these pooled analyses if they had a CAARS-Inv:SV total score at baseline and at one or more post-baseline visits at weeks 10 or 24, or had post-baseline scores that would allow missing scores at weeks 10 or 24 to be imputed. To address the primary objective, changes in functional outcomes during treatment with atomoxetine versus placebo were assessed using last observation carried forward (LOCF) analysis of covariance (ANCOVA) and mixed-effects model repeated measures (MMRM) analysis, and correlations between score changes in CAARS-Inv:SV total and functional outcomes were assessed using Spearman’s rank correlation coefficient (r) at weeks 10 and 24. The secondary objective was addressed using MMRM. Results: At baseline, patients generally had moderately severe or worse ADHD symptoms (based on CAARS-Inv:SV total scores) and impaired functional outcomes (based on Adult ADHD Quality-of-Life [AAQoL], Behavior Rating Inventory of Executive Function-Adult Version [BRIEF-A], Sheehan Disability Scale [SDS], and 36-item Short-Form Health Survey [SF-36] scores). These baseline characteristics were comparable in the atomoxetine and placebo groups. For atomoxetine versus placebo, statistically significant improvements were detected in AAQoL total and subscores at weeks 10 and 24, and in BRIEF-A Self-Report scores at week 10, but not in BRIEF-A Informant Report or SDS scores at week 10 (no BRIEF-A or SDS data were available at week 24), and not in SF-36 at weeks 10 or 24. All functional improvements were gradual. During treatment with atomoxetine, there were moderate correlations between reductions in CAARS-Inv:SV total scores and increases in AAQoL total and subscores at weeks 10 and 24 (r range -0.58 to -0.39; n = 394-545), and also with reductions in BRIEF-A Self-Report at week 10 (r = 0.49; n = 256). With placebo, moderate correlations were also found between reductions in CAARS-Inv:SV total scores and increases in AAQoL total and subscores at weeks 10 and 24 (r range -0.56 to -0.28; n = 321-542), and with reductions in BRIEF-A Self-Report at week 10 (r = 0.49; n = 271). However, correlations between changes in CAARS-Inv:SV and BRIEF-A Informant at week 10 were low for atomoxetine-treated patients (r = 0.25; n = 65), moderate with placebo (r = 0.42; n = 72), and there were low/no correlations between changes in CAARS-Inv:SV and functional outcome rating scales that are not specific to ADHD; that is, for atomoxetine-treated patients, SDS total r = 0.19 (n = 32 at week 10) and SF-36 r range - 0.20 to -0.01 (n = 51 at week 10, n = 183 at week 24). Conclusions: Atomoxetine-treated adult patients experienced improvements in functional outcomes (AAQoL and BRIEF-A Self-Report) that correlated with reductions in ADHD symptoms. Although atomoxetine improved both the ADHD symptoms and functional outcomes, the correlation between symptoms and functional outcomes was low to moderate, suggesting that they measure overlapping but different aspects of the disorder. Hence, clinicians should assess not just ADHD symptoms, but also the functional impairments.